2012
DOI: 10.1590/s1808-86942012000200016
|View full text |Cite
|
Sign up to set email alerts
|

Implante coclear em crianças pós-linguais: resultados funcionais após 10 anos da cirurgia

Abstract: The benefits of cochlear implants (CI) for communication skills are obtained over the years. There are but a few studies regarding the long-term outcomes in postlingual deaf children who grew up using the electronic device. Aim:To assess the functional results in a group of postlingual children, 10 years after using a CI. Methods:Ten postlingual deaf children, implanted before 18 years of age, participated in this study. We assessed: sentence recognition and speech intelligibility. We documented: device use an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 25 publications
(54 reference statements)
0
11
0
1
Order By: Relevance
“…21,28 According to the literature, the therapeutic process should be started as early as possible, be continuous, and involve the child's family. 3 The results of the present study showed that most children using hearing aids were still waiting for speech therapy or were receiving an inadequate number of sessions. In the state of Minas Gerais, speech rehabilitation of hearingimpaired children should be guaranteed at least twice a week by SASA or by municipalities through decentralized speech therapists.…”
Section: Discussionmentioning
confidence: 65%
See 3 more Smart Citations
“…21,28 According to the literature, the therapeutic process should be started as early as possible, be continuous, and involve the child's family. 3 The results of the present study showed that most children using hearing aids were still waiting for speech therapy or were receiving an inadequate number of sessions. In the state of Minas Gerais, speech rehabilitation of hearingimpaired children should be guaranteed at least twice a week by SASA or by municipalities through decentralized speech therapists.…”
Section: Discussionmentioning
confidence: 65%
“…Additionally, socioeconomic factors can also influence children's development. 3,36 In this study, most of the children came from families with per capita income below the minimum wage and the level of parental education was low.…”
Section: Discussionmentioning
confidence: 75%
See 2 more Smart Citations
“…Any degree of hearing loss can result in significant damage, as it interferes with perception and understanding of speech sounds. 3 The first years of life are considered critical for child development, as the peak of the central auditory system maturation process occurs during childhood and neuronal plasticity is at its maximum. 4 This makes the early detection of hearing impairment crucial to minimize the damaging impact on the development of language and listening skills, as well as on the learning process caused by hearing loss.…”
Section: Introductionmentioning
confidence: 99%